If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (9x + 8) * 2 = 9 Reorder the terms: (8 + 9x) * 2 = 9 Reorder the terms for easier multiplication: 2(8 + 9x) = 9 (8 * 2 + 9x * 2) = 9 (16 + 18x) = 9 Solving 16 + 18x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + 18x = 9 + -16 Combine like terms: 16 + -16 = 0 0 + 18x = 9 + -16 18x = 9 + -16 Combine like terms: 9 + -16 = -7 18x = -7 Divide each side by '18'. x = -0.3888888889 Simplifying x = -0.3888888889
| 13x-(5x-3)=27 | | 6(2x-7)-2(x+3)-16= | | 5(x+4)+3=7x-2(x-5) | | 4x^2=60 | | 10x-38=4x+a | | 4x-3y=7 | | 6(2x-5)-4(x+4)-16x= | | 4(3x-9)=20(x+4) | | 7-0.3x=4 | | 24x-18-16x=4(2x-5)+2 | | 34-5x=15+4x | | 7(x+3)-8=4x+3(3+x) | | 4x+y=-1 | | 80-5x=13x+18 | | 1xy^2-2x+5xy^2= | | 5(3x-8)-4(x+1)-18x= | | -4p+5+5p=12 | | 4x-1x+140=40 | | 5x^2+3x=8x | | -21=-7z | | 11-9x=159-37x | | B=qn+q | | x^2=-3x+18 | | 3(x-3)-15=0 | | 4(6z+1)-7=189 | | 27x+12=3(7x+7)+6x-9 | | 11x-(2x-7)=79 | | -6-9= | | 25=-3(22-b)+2(b-2) | | 119-5x=5x+9 | | 5n+40=45 | | k^2+3k=108 |